Immersive collaborative virtual reality for case-based graduate student teaching in thoracic surgery: A piloting study - Philipp Feodorovici; Nils Sommer; Philipp Bergedieck; Philipp Lingohr; Jörg C. Kalff; Joachim Schmidt; Jan C. Arensmeyer (Surgery Open Science)
Background: In medical education various non-digital teaching methods are established. However, studies have proven that the immersive character of virtual reality (VR) applications positively impact the understanding of spatial relationships.This study outlines the development and pilot testing of a novel system for collaborative, case-based VR teaching, utilizing real-time volume rendered computed tomography (CT) data of thoracic cases among graduate students. Methods: A system was configured and deployed to provide real-time volume rendered CT data in a collaborative, multiuser VR environment. A thoracic surgery VR course was implemented into the surgical graduate curriculum, which has subsequently been evaluated with questionnaires. Results: Seventy students assessed the curriculum through a questionnaire. Usability was rated intuitive (77.14 %) while few students (5.71 %) reported cyber sickness.A vast majority (98.57 %) agreed VR improved their understanding of anatomy compared to traditional methods and most students found learning more effective. (88.57 %) and joy during participation was rated high (97,14 %). A majority of the students (61.43 %) believed VR could partly replace traditional methods. They supported integrating VR into preclinical (81.43 %) and clinical teaching (94.29 %) as well as taking VR courses from home (78.57 %). Most participants (90,72 %) encouraged the expansion of VR infrastructure. Conclusion: The concept of a collaborative real-time VR-based educational program in medical graduate teaching has proven its technical feasibility and positive acceptance with a desire for more VR integration in surgical curricula. A two-armed study will be conducted to evaluate the objective impact as the expansion of VR environments for teaching continues.